Effects of Taurine on Primary Metabolism and Transcription in a Coral Symbiodinium sp. - Huang, Aiyou; Shi, Hejing; Cui, Ruoxuan; Cai, Xiaoni; Xie, Zhenyu (Frontiers in Microbiology, 2022)
Coral reefs belong to the marine ecosystems and host the richest biodiversity of marine organisms. Coral reefs are formed as a result of the symbiotic relationship between the host coral animal and photosynthetic dinoflagellates, namely Symbiodinium sp. Coral animals induce the release of carbon fixation products of symbiotic Symbiodinium sp. through secreting host release factors (HRFs) such as taurine. To study the potential effect of taurine on photosynthesis and release of carbon fixation products of Symbiodinium sp., we compared the growth of Symbiodinium sp. under control and taurine-stimulated conditions. Photosynthesis parameters were detected to monitor the photosynthetic efficiency. Biomass and the contents of total soluble sugar, total insoluble sugar, total protein, total lipids, chlorophyll a were analyzed. Metabolome and transcriptome analyses were performed to analyze the potential effect of taurine on primary metabolism and mRNA transcription. The results revealed that taurine significantly increased the growth, photosynthesis efficiency, total soluble sugar, chlorophyll a, and chlorophyll b and free amino acid content of Symbiodinium sp. while decreased the content of total insoluble sugar. Results of metabolome and transcriptome analyses suggested that taurine might affect metabolic pathways in Symbiodinium sp. by altering the permeability of the algal cell membrane, diverting photosynthetically fixed carbon from storage compounds to translocated compounds, releasing a signal of low concentrations of nitrogen to initiate a series of response mechanisms, and controlling the density of Symbiodinium sp. through the quorum sensing effect. These results help to explore how corals control carbon metabolism in Symbiodinium sp. and to provide theoretical guidance for furthering our understanding of Symbiodinium sp. biology and coral-algal symbiosis.